Its factors would be
(x+2)*(x-1)*(x+0)
x^2 +x -2
x^3 + 0 + x^2 + 0 -2x +0
Equation: x^3 + x^2 -2x
f(2) = 8 + 4 -4
2x^3 + 2x^2 -4x +0
f(2) = 16 + 8 -8
3x^3 + 3x^2 -6x +0
f(2) = 24 +12 -12
4x^3 + 4x^2 -8x +0
f(2) = 32 +16 -16
So, the equation is:
4x^3 + 4x^2 -8x = 0
Do you have a photo or something?
The answer should be 32.25
A ratio is comparison between two number such as
I have three dogs and two cats the ratio of cats to dogs is 2:3 or what is the ratio of cats to total pets which is 2;5
Step-by-step explanation:
f(x)=2x²+3x+9
g(x) = - 3x + 10
In order to find (f⋅g)(1) first find (f⋅g)(x)
To find (f⋅g)(x) substitute g(x) into f(x) , that's for every x in f (x) replace it by g (x)
We have
(f⋅g)(x) = 2( - 3x + 10)² + 3(- 3x + 10) + 9
Expand
(f⋅g)(x) = 2( 9x² - 60x + 100) - 9x + 30 + 9
= 18x² - 120x + 200 - 9x + 30 + 9
Group like terms
(f⋅g)(x) = 18x² - 120x - 9x + 200 + 30 + 9
(f⋅g)(x) = 18x² - 129x + 239
To find (f⋅g)(1) substitute 1 into (f⋅g)(x)
That's
(f⋅g)(1) = 18(1)² - 129(1) + 239
= 18 - 129 + 239
We have the final answer as
<h3>(f⋅g)(1) = 128</h3>
Hope this helps you